A case control study on the effect of Diabetes and Hypertension on oral health - S, VAISHALI.; CHAUDHARY, MANJARI; DURAISAMY, REVATHI (The journal of contemporary issues in business and government, 2021)
Diabetes and hypertension causes dysfunction in oral components like salivary glands and oral mucosa. Patients with poorly controlled glycemia may present reduction of salivary flow rate and as a consequence, an increased risk to develop oral injuries and impairment on velocity and quality of wound healings. . Moreover, presence of hypertension increases the probability of xerostomia (associated or not to salivary flow deficiency) as the number of cardiovascular drug administration increases. The aim of the study is to evaluate the effect of diabetes and hypertension on oral health. It is a university setting study. 300 patients who reported to a private dental college with diabetes, hypertension and both, 100 in each group were randomly selected. The periodontal status and the radiographs of these patients were collected after reviewing case sheets of patients and compared with their medical condition using Chi square test and analysed. The results were represented in the form of bar graphs. The age group which was most commonly affected was 51-60 years (37%). Males (53%) were most affected when compared to females (46%). Generalised chronic periodontitis was mostly seen in patients with both diabetes and hypertension (77%) but was not statistically significant (p>0.50). Radiovisiography / Orthopantomogram was mostly taken for patients with diabetes (17%) and for those patients who had generalised chronic periodontitis (24%). Within the limits of the study, periodontal destruction is increased in patients with both diabetes and hypertension, as compared to patients with diabetes alone and hypertension alone.